2008
DOI: 10.1111/j.1745-9133.2008.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

The Miracle of the Cells: An Experimental Study of Interventions to Increase Payment of Court‐ordered Financial Obligations*

Abstract: Jersey AOC as a response to concerns among probation personnel that probationers sentenced to monetary penalties often failed to meet their financial obligations. The program sought to increase payment of court-ordered financial obligations among probationers who are seriously delinquent in paying fines, penalties, and restitution, and was designed to "strengthen the effectiveness of restitution and fine sanctions by forcing those offenders who have the ability to make regular payments to do so." Project MUSTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 25 publications
1
56
0
Order By: Relevance
“…The one exception may involve short prison sentences. The fine payment experiment conducted by Weisburd et al (2008) and the Project Hope experiment make it clear that the imminent threat of incarceration is a powerful incentive for paying delinquent fines or for conforming with conditions of probation even for populations who have not been deterred previously by the threat of punishment. These experiments suggest that there is a concave relationship between the magnitude of deterrent effects and sentence lengths.…”
Section: Estimating the Deterrent Effect Of Shorter Prison Sentences mentioning
confidence: 99%
“…The one exception may involve short prison sentences. The fine payment experiment conducted by Weisburd et al (2008) and the Project Hope experiment make it clear that the imminent threat of incarceration is a powerful incentive for paying delinquent fines or for conforming with conditions of probation even for populations who have not been deterred previously by the threat of punishment. These experiments suggest that there is a concave relationship between the magnitude of deterrent effects and sentence lengths.…”
Section: Estimating the Deterrent Effect Of Shorter Prison Sentences mentioning
confidence: 99%
“…Lochner (2007) found evidence for certainty effects in the National Longitudinal Survey of Youth and National Youth Survey, and Matsueda, Kreager, and Huizinga (2006) reported certainty effects in the Denver Youth Study. In a randomized natural experiment, Weisburd, Einat, and Kowalski (2008) found that probationers in New Jersey who were randomly selected to experience an increased likelihood of violation to prison for nonpayment of fines (and informed of this) were substantially more likely than the remaining probationers to pay their fines. Literature reviews by Nagin (1998), Bushway and Reuter (2008), Matsueda (in press), McCarthy (2002), Piquero, Paternoster, Pogarsky, and Loughran (in press), and Paternoster (2010) each identify evidence for deterrence and rational choice principles.…”
Section: Introductionmentioning
confidence: 98%
“…Three studies nicely illustrate heterogeneity in the deterrence response to the threat of imprisonment: the Weisburd et al (2008) study on the use of imprisonment to enforce fine payment finds a substantial deterrent effect, the Helland and Tabarrok (2007) analysis of the deterrent effect of California's third strike provision finds only a modest deterrent effect, and the Lee and McCrary (2009) examination of the heightened threat of imprisonment that attends coming under the jurisdiction of the adult courts at the age of majority finds no deterrent effect. Weisburd et al (2008) report on a randomized field trial of alternative strategies for incentivizing the payment of courtordered fines.…”
Section: The Deterrent Effect Of Imprisonmentmentioning
confidence: 99%
“…Weisburd et al (2008) report on a randomized field trial of alternative strategies for incentivizing the payment of courtordered fines. The most salient finding involves the 'miracle of the cells,' namely, that the imminent threat of incarceration is a powerful incentive for paying delinquent fines.…”
Section: The Deterrent Effect Of Imprisonmentmentioning
confidence: 99%